Каково качество гражданственности нашего общества? Измерение активной гражданской позиции - Анди Ахмад Яни; Анди Хидаят (Вопросы государственного и муниципального управления, 2018)
Citizenship is a core value of a democratic system that shapes political behavior of community members to be actively involved in the decision-making process and promote collaboration and reciprocity. However, we do not know how to assess the quality of the citizenship of our community. We need a method to analyze the degree of citizenship quality in order to ensure a sustainable and democratic environment. This study proposes a Citizenship Index based on the citizenship concept of Bellamy (2008) for measuring the degree of citizenship. Bellamy (Ibid) addresses three main indicators of citizenship: membership of a political community;  collective duties and rights as a consequence of membership; and participation in the social and political process. The study was conducted in September-October 2016 using a survey method and 429 respondents who are citizens of Makassar City, Indonesia were interviewed. Based on the three variables of Bellamy’s citizenship concept, this study found that the citizenship quality of Makassar citizens is active and strong in terms of getting engaged in development programs of the Makassar government. Moreover, Makassar citizens are altruistic and eager to collaborate with people from ethnicities and religious backgrounds. This method can help decision-makers to analyze and map the citizenship quality of a particular community as a consideration in formulating and implementing further public policies.